Gas sensing using porous materials for automotive applications. (7th July 2015) - Wales, Dominic J.; Grand, Julien; Ting, Valeska P.; Burke, Richard D.; Edler, Karen J.; Bowen, Chris R.; Mintova, Svetlana; Burrows, Andrew D.
<x xml:space="preserve">Abstract</x> The use of zeolites and metal–organic frameworks in the sensing of gases emitted from automobile exhausts is reviewed.